Desert sand stabilization using biopolymers: review - Monika Dagliya; Neelima Satyam; Ankit Garg (Smart Construction and Sustainable Cities)
Abstract Wind-driven sand erosion is the leading primary reason of earth deterioration in dry lands and a major global issue. Desert dust emissions and topsoil degradation caused by wind pose a global danger to the ecosystem, economy, and individual health. The aim of the current study is to critically analyze the different types of biopolymers and their interaction mechanism with sands for desert sand stabilization. Extensive experimental data with different percentages of biopolymers has been presented on various wind erosion studies using wind tunnel testing and their control rate on desert sand stabilization. Also, studies related to evaluating the engineering properties of sand using biopolymers were analyzed. Other biological approaches, namely Microbial-induced calcite precipitation (MICP) and Enzyme-induced carbonate precipitation (EICP), have been discussed to regulate wind-driven sand erosion in terms of percentage calcite formation at different compositions of urea and calcium chloride. Comparative analysis of MICP and EICP with biopolymer treatment and their limitations have been discussed. Biopolymers are not only demonstrated adeptness in engineering applications but are also helpful for environment safety. Biopolymers are suggested to be novel and nature-friendly soil-strengthening material. This review focuses on the fundamental mechanisms of biopolymer treatment to reduce wind-driven sand loss and its future scope as a binder for sand stabilization. The mechanism of soil-biopolymer interaction under various soil conditions (water content, density, and grain size distribution) and climatic circumstances (drying-wetting cycles) needs to be explored. Furthermore, before applying on a large scale, one should evaluate sand-biopolymer interaction in terms of durability and viability.